Selected β-glucans act as immune-training agents by improving anti-mycobacterial activity in human macrophages - a pilot study. - Clara Braian; Lovisa Karlsson; Jyotirmoy Das; Maria Lerm (Karger Publishers, 2023)
Epigenetic reprogramming of innate immune cells by β-glucan in a process called trained immunity, leads to an enhanced host response to a secondary infection. β-glucans are structural components of plants, algae, fungi and bacteria and thus recognized as non-self by human macrophages. We selected the β-glucans curdlan from Alcaligenes faecalis, WGP dispersible from Saccharomyces cerevisiae, and β-glucan-rich culture supernatant of Alternaria and investigated whether they could produce trained immunity effects leading to an increased control of virulent Mycobacterium tuberculosis. We observed a significant M. tuberculosis growth-reduction in macrophages trained with curdlan and Alternaria, which also correlated with increased IL-6 and IL-1β release. WGP dispersible-trained macrophages were stratified into 'non responders' and 'responders', according to their ability to control M. tuberculosis, with 'responders' producing higher IL-6 levels. The addition of neutrophils to infected macrophage cultures further enhanced macrophage control of virulent M. tuberculosis, but not in a stimuli-dependent manner. Pathway enrichment analysis of DNA methylome data also highlighted hypomethylation of genes in pathways associated with signaling and cellular reorganization and motility, and 'responders' to WGP-training were enriched in the interferon-gamma signaling pathway. This study adds evidence that certain β-glucans show promise as immune training agents.